THEORETICAL AND METHODICAL BASIS OF CHOREOGRAPHIC PREPARATION IN TECHNICAL-AESTHETIC SPORT - Valentyna Todorova; Tetiana Pasichna (Lesya Ukrainka Volyn National University, 2017)
The research goal is to model a system of choreographic training in techno-aesthetic kinds of sport. Materials and methods: systematization of scientific sources on the problem under study; method of pedagogical modeling. Results: In this paper, the scientific and methodological justification of the choreographic training system as a purposeful controlled process proceeds from the theory of general training of athletes. It ensures the unity of the stages and unites them into a continuous pedagogical process, makes it possible to consider choreographic training as an integral system with the prediction of choreographic preparedness control in evaluating the indicators of the component criteria; selection of choreographic instruments taking into account the levels of formation of criteria for choreographic preparedness; content and variational methodological support for choreographic training at various stages of multi-year training. Conclusions: a modelled system of choreographic training, which can simultaneously be considered as a separate independent element, and as a component of the general system of training of athletes.